Critical Success Factors of Green Building Retrofitting Ventures in Iraq - Alfaiz, Sundus Khaleel; Abd Karim, Saipol Bari; Alashwal, Ali Mohamed (International Journal of Sustainable Construction Engineering and Technology, 2021)
Climate change has become one of the challenges for development. The building sector represents the largest resource of greenhouse gas production. Iraq depends on fossil fuels in producing energy, electricity with a lack of energy standards. This has made Iraq one of the utmost carbon-intense economic in the world. There is a lack of studies about green building retrofitting (GBR) projects in Iraq as well as lack of awareness about the importance of this concept and its welfare regarding the reduction of the climate change crisis. The enhancement of the implementation of GBR projects in Iraq will be a promising solution to overcome the negative impact of the existing buildings. The GBR projects represent a complicated project that needs an effective project management practices. It is crucial to identify the challenges that restrict the success of these ventures. This paper provides critical success factors (CSF) that will stimulate the achievement of GBR ventures in Iraq. A questionnaire survey is conducted to collect reliable data from the experts in retrofitting projects in Basra, Iraq. Findings showed that the top five challenges in implementing GBR are; absence of government legislation, lack of awareness about benefits of GBR, low government and private sectors’ investment, incompetent team members, and lack of sustainability knowledge. Additionally, the top five CSFs are; efficient legislation, competent team members, subsidies or tax reduction, sufficient experience and competence of the project manager. This research will contribute to the improvement of project management practices in GBR projects, reduction of environmental pollution and enhancement of Iraq’s oil revenues instead of using oil as energy fuel.